New information on taxonomy status of the species in the family Gracilariaceae (Rhodophyta) of Vietnam - Hau, Le Nhu (Academia Journal of Biology, 2012)
After re-examination of all herbarium specimens and new collected materials, based on the morphological comparison and mocecular analysis we have identified 14 species of a total 33 species of the family Gracilariaceae previously identified by other authors and added 6 species as the new record for marine algae flora of Vietnam and thus up to now there are a total of 20 marine algae species recorded for Vietnam. Six algae species newly recorded from Vietnam are Gracilaria cuneifolia (Okamura) Lee & Kurogi, Gracilaria longirostris Zhang & Wang, Gracilaria rubra Chang & Xia, Gracilaria yamamotoi Zhang & Xia, Hydropuntia divergens (Xia & Abbott) Wynne and Gracilariopsis nhatrangensis Le & Lin. The list of 20 algae species with old misidentified names is aldo provided.